COP-27: A great opportunity to address the double crisis of food security and climate change–and for the EU to re-align its farm to fork strategy - Aerni, Philipp (Frontiers in Environmental Economics, 2023)
The 27th Conference of the Parties (COP 27) of the UN Framework Convention on Climate Change (FCCC) held in November 2022 in Sharm-el-Sheik, Egypt, ended with joint commitments to compensate for loss and damage and increase funds for climate change adaptation in future. This outcome is likely to be supportive of current efforts to render agricultural systems in low income tropical countries more resilient and productive through locally adapted forms of sustainable intensification. However, the farm-to-fork (f2f) strategy launched in 2020 by the European Union (EU) has set targets that associate sustainable agriculture primarily with extensification rather than intensification. This paper critically reviews the literature that assesses the impact of current agricultural, environmental and development policies on global food security, biodiversity and climate change. It challenges the view that the European Green Deal and the f2f strategy will have its desired effects. It also argues that the intention of the European Commission (EC) to promote the f2f strategy in low income tropical countries may not be compatible with its commitment to the ownership principle in development assistance. The decision of the EC in fall 2022 to propose a regulatory framework on new breeding techniques (NBTs) indicates that methods of sustainable intensification may be reconsidered if they serve the goals of the Green Deal and the f2f strategy. Such a readjustment would also be in line with the outcome of COP27 and indicate that the polarized global debate on sustainable food systems may become more pragmatic and outcome-oriented again.